Effect of different sowing schedule and crop geometry on productivity andprofitability of Indian mustard (Brassica juncea L.): SOWING SCHEDULE AND CROP GEOMETRY IN INDIAN MUSTARD - A L JAT,; A G DESAI,; B S RATHORE, (Journal of Oilseeds Research, 2019)
A field experiment was conducted during three consecutive rabi seasons of 2014-15 to 2016-17 to study the effect of different sowing dates and crop geometry on productivity and profitability of Indian mustard (Brassica juncea L.) at Castor-Mustard Research Station, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar in the north-Gujarat agro-climatic region. The experiment was laid out in split plot design with 3 sowing dates and 5 planting geometry replicated thrice. Results revealed that sowing of mustard crop in the second fortnight ofOctober during all three years produced significantly higher seed yield (1882 kg/ha). Among the planting geometry, significantly higher seed yield, was recorded with 30 cm× 10 cmfollowed by 45 cm × 15 cm as compared to rest of the spacing. Similar trend followed for net returns and B: C ratio.